Long‐term prophylaxis in severe factor VII deficiency. (8th May 2015) - Siboni, S. M.; Biguzzi, E.; Mistretta, C.; Garagiola, I.; Peyvandi, F.
<x xml:space="preserve">Abstract</x> Introduction The spectrum of bleeding problems in FVII deficiency is highly variable and FVII levels and causative genetic mutations correlate poorly with the bleeding risk. Long‐term prophylaxis is generally initiated in order to prevent subsequent CNS bleeding after a first event or in patients with other major/ life threatening/ frequent bleeding symptoms as gastrointestinal bleeding or hemarthrosis. However few data are available in the literature regarding FVII prophylaxis and clinical decisions cannot be based on evidence. Aims We report the data available in the literature on FVII prophylaxis and our personal experience regarding three patients affected by severe FVII deficiency. Methods Specific papers on long‐term prophylaxis in severe FVII deficiency were identified using the database, PUBMED. Results The most frequent indications for long‐term prophylaxis were CNS bleeding (58%), hemartrosis (15%) and GI bleeding (9%). Patients were treated with various dosages and frequency. Prophylactic treatment with 10‐30U/kg (pdFVII) or 20‐30mcg/kg (rFVIIa) twice or three times/weeks was described to be effective. Conclusions In the literature and in our experience, prophylaxis can be considered in patients with severe FVII deficiency and severe bleeding phenotype. A dose of 10‐30U/kg (pdFVII) or 20‐30 microg/kg (rFVIIa) twice or three times/week is usually administrated, but dose and frequency can be tailored based on the clinical follow‐up of the patients. Since hemarthrosis is a frequent manifestation, a suggestion to improve the outcomes of patients with severe FVII deficiency is to monitor joint condition in order to identify early arthropathy that could be another indication to start secondary prophylaxis.